The efficacy of helbo therapy in the treatmentof periodontal tissue diseases after coronavirus disease - Matviykiv Т. І.; Rozhko М. М.; Kateryniuk В. Ю. (Actual Dentistry, 2022)
The pathogenesis and clinical course of chronic generalized periodontitis due to coronavirus disease acquires rapidly progressive signs, which significantly reduces the quality of life in the postcovid period and requires scientists to find other effective, minimally invasive techniques that will complement and increase the effectiveness of such treatment for patients, that will reduce the usage of pharmaceutic drugs. Relevant, in this context, technique to which attention should be paid is Helbo therapy, using a laser «Helbo Thera Lite», which has a wide range of advantages over analogues. Changes in periodontal indices after a comprehensive dental treatment with additional inclusion of the course of Helbo therapy and the appointment of a corrective treatment complex have a significant tendency to improve the clinical picture in the oral cavity, which makes the use of this technique especially relevant. It will facilitate the introduction of the proposed treatment regimens of chronic generalized periodontitis in the postcovid period to the dentists in the future.